泰文學習拼字系統之創新教學：泰語學習自我效能、學習興趣、學習焦慮及學習成就之相關研究 Exploring Learning Effect on Innovative Thai Spelling System: Correlates Among Learning Self-Efficacy, Learning Interest, Learning Anxiety, and Learning Achievement - 譚華德 Nitiwat Watthanapas; 郝永崴 ung-Wei Hao; 黃明月 Ming-Yueh Hwang (National Taiwan Normal University, 2019)
本研究乃發展一套適用於中文母語者的自然發音泰文學習拼字系統，並應用認知─情意學習理論，檢測此教學系統當中，學習者的泰語學習自我效能、學習興趣、學習焦慮及學習成就之間的關係。經立意取樣方式，於臺灣北部地區三所大學進行九週的教學實驗，每週課程時間為 2 小時，共 183 位有效參與者，學習者需協助完成學習情意表現因素之相關問卷，所得資料經由 SPSS 23 進行信度與效度檢驗，再透過 AMOS 20 進行結構方程模型驗證。研究結果顯示：一、泰語學習自我效能與學習興趣呈現正相關；二、泰語學習自我效能與學習焦慮呈現負相關；三、泰語學習興趣與學習成就呈現正相關；四、泰語學習焦慮與泰語學習成就呈現負相關。此外，與其他泰文拼字系統相較，本研究開發的系統將可進一步應用於其他泰文教學環境。 This study developed a Thai spelling system to facilitate natural pronunciation among native Chinese speakers. It applied the cognitive-affective theory of media learning to explore the effect of this system on learning outcomes. Specifically, with regard to the Thai language, we examined correlations between self-efficacy, learning interest, learning anxiety, and learning achievement. A weekly two-hour teaching course was conducted over nine weeks at three universities in northern Taiwan. Data were gathered using a questionnaire, and they were tested for reliability and validity using SPSS, version 23, after which they results were verified through structural equation modeling using AMOS 20. One hundred eighty-three valid questionnaire responses were collected from participants. Results indicated that (1) Thai learning self-efficacy is positively related to Thai language learning interest, (2) Thai language learning self-efficacy is negatively related to Thai language learning anxiety, (3) Thai language learning interest is positively related to Thai language learning achievement, and (4) Thai language learning anxiety is negatively related to Thai language learning achievement. Compared with other Thai spelling systems, the system developed in this study is more effective and should be used for native Chinese learners of Thai.